2006
DOI: 10.1002/jgm.904
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐tumor efficacy of a transcriptional replication‐competent adenovirus, Ad‐OC‐E1a, for osteosarcoma pulmonary metastasis

Abstract: These data demonstrated that OC promoter could direct adenovirus replication by controlling the E1a gene to target human OSPM in a tumor-specific manner, providing an efficient tool to develop a feasible therapeutic modality for OSPM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Adenovirus-mediated gene therapy has been tested broadly in clinical trials, and tumor/tissue-restricted replicative adenovirus showed significant advantages over replication-deficient adenovirus (14,28,29). However, the single administration of PRRA ultimately results in failure due to inefficient viral distribution in tumor masses (12,14).…”
Section: Discussionmentioning
confidence: 99%
“…Adenovirus-mediated gene therapy has been tested broadly in clinical trials, and tumor/tissue-restricted replicative adenovirus showed significant advantages over replication-deficient adenovirus (14,28,29). However, the single administration of PRRA ultimately results in failure due to inefficient viral distribution in tumor masses (12,14).…”
Section: Discussionmentioning
confidence: 99%
“…Recently in this model the CRAd Ad-OC-E1a construct was evaluated and showed a significant decrease in tumor nodules. Moreover, normal lung tissue was not affected when using this intravenous administrated vector (84). In addition, the canine model developed by us (59) should be a valuable model to study delivery in an immune-competent context as canine OS bears a striking resemblance to human OS and thus will be a useful model for testing gene therapy approaches.…”
Section: Gene Deliverymentioning
confidence: 96%
“…In addition, the promoter of the CREBBP/EP300 inhibitory protein 1 (CRI1), a gene specifically expressed in malignant pleural mesothelioma, was used to drive E1a-mediated virotherapy that specifically kills malignant mesothelioma cells but not normal cells [83]. Other tumor-specific promoters used to drive E1-mediated virotherapy against various cancers include mucin-1 promoter [84], osteocalcin promoter [85], AFP promoter [55], midkine promoter [86] and COX-2 promoter [87,88]. In general, regulation of therapeutic transgene expression (such as E1a) by a tumor-specific promoter is preferred over tissue-specific promoter strategy for several reasons: i) not all tissue-specific promoters are available for every organ/tissue; ii) only a few of organs/ tissues are dispensable, such as the prostate, while most serve critical life-sustaining functions; and iii) tumorspecific promoters that express only in cancer cells, not (or express at a much lower level) in normal cells, such as telomerase and survivin, provide an ideal tumor targeting with minimal toxicity and maximal anticancer effect.…”
Section: Tumor-specific Targeting and Cancer Virotherapymentioning
confidence: 99%